Studi In Silico : Potensi Anthelmintik Senyawa Aktif Bawang putih (Allium sativum L.) dalam Menghambat Protein Target Acetylcholinesterase, Beta tubulin dan Aktivasi Voltage dependent L type Calcium Channel - Sita Az Zahra Mubarika; Ariani Ratri Dewi; Dini Sri Damayanti (Jurnal Kedokteran Komunitas, 2020)
Introduction: The tuber of garlic contains of various compounds that has anthelmintic effect of unknown mechanism.  Therefore, this research aimed to determine the active compounds and find their anthelminthic mechanism of action. Method: The potency of garlic active compounds to inhibit acetylcholinesterase, beta tubulin and to activate voltage dependent L type calcium channel were evaluated by molecular docking, compared with pirantel pamoat, mebendazole and praziquantel.Result:  Garlic’s active compound, S-allyl-cysteine sulfoxide (alliin) has the best affinity to target protein acetylcholinesterase, beta tubulin and calcium channel with free binding energy of -4.84 kcal / mol, -5.89 kcal / mol and 6.50 kcal / mol respectively under control values. Active compounds of bawang putih tuber have lower affinity values compared to controls of pyrantel pamoate, mebendazole and praziquantel.Conclusion: Active compounds of bawang putih (Alliium sativum L) have low antihelmintic potential through target protein acetylcholinesterase, beta tubulin and voltage dependent L type calcium channel. Keyword: Anthelmintik, Allium sativum L., in silico